2017
DOI: 10.1159/000454819
|View full text |Cite
|
Sign up to set email alerts
|

Universal Sustained Viral Response to the Combination of Ombitasvir/Paritaprevir/Ritonavir and Dasabuvir with/without Ribavirin in Patients on Hemodialysis Infected with Hepatitis C Virus Genotypes 1 and 4

Abstract: Background: Hepatitis C virus (HCV) infection is highly prevalent among patients on hemodialysis (HD) and is associated with poor prognosis. Treatment with interferon and ribavirin is poorly tolerated, and few data are available on the impact of new direct-acting antivirals (DAAs). This study was intended to analyze the efficacy and safety of treatment with a combination of ombitasvir/paritaprevir/ritonavir and dasabuvir with/without ribavirin in HCV-infected patients on HD from 3 hospitals. Methods: This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
3
14
1
1
Order By: Relevance
“…Our study showed that the SVR 12 rate of PrOD for 12 weeks was excellent (100%) for East Asian HCV GT1b non-cirrhotic patients receiving hemodialysis and was comparable with the response rates in clinical trials and real-world studies. 14,[17][18][19][20] The SVR 12 rate in our study was 36% higher than the response rate of 64% by pegylated IFN/RBV therapy. Based on the excellent efficacy, applying PrOD would be a preferred choice for treating East Asian HCV GT1b non-cirrhotic patients receiving hemodialysis.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our study showed that the SVR 12 rate of PrOD for 12 weeks was excellent (100%) for East Asian HCV GT1b non-cirrhotic patients receiving hemodialysis and was comparable with the response rates in clinical trials and real-world studies. 14,[17][18][19][20] The SVR 12 rate in our study was 36% higher than the response rate of 64% by pegylated IFN/RBV therapy. Based on the excellent efficacy, applying PrOD would be a preferred choice for treating East Asian HCV GT1b non-cirrhotic patients receiving hemodialysis.…”
Section: Discussioncontrasting
confidence: 61%
“…Following the clinical trials that demonstrated the excellent efficacy and safety profiles, the real-world effectiveness of PrOD in HCV GT1 patients receiving hemodialysis from Spain, Czech Republic, and Saudi Arabia showed that the SVR 12 rates ranged from 96% to 100%. [17][18][19][20] However, data regarding the efficacy and safety of PrOD for HCV GT1b patients receiving hemodialysis are lacking in East Asia, where HCV GT1b infection is prevalent. We aimed to conduct a clinical trial to assess the performance of PrOD for 12 weeks in HCV GT1b non-cirrhotic patients receiving hemodialysis in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Similar SVR rates (excellent or absolute) were described in two real-life cohorts of haemodialysed patients: the SVR rate in the study by Muñoz-Gómez et al [15] was 95.7%, where 2 out of 46 patients discontinued treatment for non-virological reasons, but the analysis evaluated patients infected with genotypes 1 and 4 together. Abad et al [14] achieved an absolute SVR rate in a group of 35 haemodialysed patients infected with genotypes 1 and 4. The explanation for the 100% SVR rate in our group of patients may be due to our patients being predominantly infected with HCV subtype 1b (20 of 23, 87%).…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia was the most common AE in the RUBY-I study, and RBV was interrupted in 9 out of 13 HCV subtype 1a patients to whom RBV was administered [13]. In the study by Muñoz-Gómez et al [15], 16 out of 27 patients receiving ESA (10 of them treated with RBV), and in the study by Abad et al [14], 15 out of 28 patients receiving ESA needed an increase of the ESA dose. We assume that the reduced RBV dose was the reason for different AEs profile in our cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation